Phân tích phân cụm các doanh nghiệp ở Việt Nam, Thái Lan và Indonesia trong giai đoạn 2018–2022: Ứng dụng phương pháp phân tích dữ liệu đa hợp - Đào Thị Thanh, Bình; Nguyễn Anh, Tuấn; Phạm Văn, Hùng; Lê Thanh, Bình (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The study focuses on using financial indicators to analyze the clustering of businesses, employing a compositional data analysis method. With data taken from the financial reports of 300 large enterprises in Thailand, Indonesia, and Vietnam, the study aims to cluster the enterprises and thereby understand the characteristics of each cluster as well as the movement of enterprises between clusters during the period 2018-2022. The results obtained show no significant difference when using both CLR and ALR methods, the financial indicators are effective in classifying companies, dividing them into three clusters based on business efficiency and financial risk levels. Analysis in the pre-COVID-19 and post-COVID-19 periods also shows signs of recovery in business results through the clustering shifts of some companies. Notably, Vietnamese businesses demonstrate good operational performance and maintain a significant presence in the group with the best performance results and high payment safety.
Keywords: Compositional data analysis; Cluster analysis; Financial ratios; Business classification; COVID-19